Optimization of ingredients for Lactobacillus fermented beverages - Olsson,Rebecka (2017)
The ingredients generally used in the fermentation of probiotics tend to give an off-flavour to the fermentation product which is not ideal when producing e.g. fruit drinks. The aim of this master thesis was to evaluate if the concentration of such ingredients could be lowered and also to investigate whether there are other ingredients that could act as substitutes to those ingredients giving off-flavours. The growth, stability and taste of the fermentation products containing the ingredients and probiotics, as well as the fermentation product put in a fruit model system, was evaluated. The experimental work included changing the concentration of the ingredient giving the off-flavour and exchanging it with substituting ingredients during the fermentation of three different probiotic bacteria. The bacterial content was measured using a plate count method and the stability of the fermentation product was evaluated after one week of storage in 4C. After putting the fermentation product in a fruit juice, the stability was measured during four weeks of storage and a simplified sensory evaluation was done. It was found that the ingredients that gave the significantly highest growth was generally the ingredient normally used during the fermentation and none of the substituting ingredients were as successful in supporting growth. It was also concluded that the type of bacteria will have an effect on the final bacterial content in the fermentation product and the sensory properties where some strains had a better taste profile than others.